A preliminary numerical investigation of airborne droplet dispersion in aircraft cabins - Bhatia, Dinesh; De Santis, Antonio (Scientific Research Publishing, 2020)
The emergence of the novel coronavirus has led to a global pandemic which has led to the airline industry facing severe losses. For air travel to recover, airlines need to ensure safe air travel. In this paper, the authors have modelled droplet dispersion after a single breath from an index patient. Computational Fluid Dynamics (CFD) simulations are conducted using the k-w SST turbulence model in ANSYS Fluent. The authors have taken into consideration several parameters such as the size of the mouth opening, the velocity of the cabin air as well as the number of droplets being exhaled by the index patient to ensure a realistic simulation. Preliminary results indicate that after a duration of 20s, droplets from the index patient disperse within a 10 m2 cabin area. About 75% of the droplets are found the disperse for up to 2m axially behind the index patient. This could possess an enhanced risk to passengers sitting behind the index patient. Ultimately, this paper provides an insight into the potential of CFD to visualise droplet dispersal and give impetus to ensuring necessary mitigating measures can be taken to reduce the risk of infection through droplet dispersal.